Morphometrical parameters of acetabulum of hip bone - An osteological study - Meril Ann Soman,; Rani Nallathamby,; Shivarama Bhat,; Godly Sara Sabu, (Asian Journal of Medical Sciences, 2023)
Background: Acetabulum is an approximately hemispherical cavity on the lateral aspect of the hip bone. Acetabulum is not always of the same shape, size, or depth. Any deviations of the parameters from normal range have strong correlation with the development of various kinds of pathologies. Aims and Objectives: Acetabulum is an approximately hemispherical cavity on the lateral aspect of the hip bone. Acetabulum is not always of the same shape, size or depth. Any deviations of the parameters from normal range have strong correlation with the development of various kinds of pathologies. Materials and Methods: This study was conducted in department of Anatomy, Yenepoya Medical College, Mangalore. Two hundred hip bones were included in the study. Various parameters of the acetabulum were measured. The morphometrical parameters measured were: (a) Transverse diameter of acetabulum, (b) acetabular height, (c) acetabular depth, (d) acetabular volume, (e) distance from pubic tubercle to anterior rim of acetabulum, (f) ratio between distance from pubic tubercle to anterior rim of acetabulum and acetabular height. Range, mean, standard deviation, and standard error of mean were determined for each parameter. P value was also calculated to compare the parameters side wise. Results: The independent T test was done and the P value was calculated for each parameter. Acetabular volume showed a significant difference between left- and right-sided bones. Most of the parameters showed highly significant difference between male and female hip bones in both right side and left side. Conclusion: As total and partial hip replacements are common surgeries performed these days, knowledge of the dimensions of acetabulum will assist prosthetists to construct suitable prosthesis for Indian population. It would be also useful in the fields of anatomy, osteology, and anthropology.